PENGEMBANGAN MULTIMEDIA INTERAKTIF MODEL TUTORIAL - Desma Viana Sari; Agus Suyatna; Feriansyah Sesunan (Jurnal Pembelajaran Fisika, 2013)
This developmental research was intended to make an interactive multimedia tutorial model by using Microsoft PowerPoint for SMP/MTs on the static and dynamic electricity subjects that contain materials, interactive animation, virtual labs, exercises, and competence test. This design of evelopmental research modified the process of the instructional media development developed by Sadiman, et al. With the stages of work procedure that comprise needs analysis, objectives, materials, synopsis, initial script, prototype production, evaluation consisting of three phases, namely the material expert test, the design expert test, and one on one expert test. This also includes revision, final script, trials, and final program. The result of one on one test stating that this interactive multimedia has an interesting quality, easy to use,and it is very useful. It is also the same with the result of field test that also has an interesting quality, easy to use, and it is very useful also.From the result of the field test can be concluded that this interactive multimedia is very effective to beused as a learning resource. Keywords: research and development, interactive multimedia, tutorial model,static electricity and electric dynamic SMP/MTs.